Interrelationships Among Marketing Mix Strategies, Service Quality and Firms’ Business Performance in Readymade Garments Sector, Bangladesh - Karim, Rashed; Jahan , Nusrat; Jebunnesa, Ummea; Lepee, Nusrat Jahan (Journal of Technology Management and Business, 2023)
The garment industry in Bangladesh has experienced substantial growth over the past three decades. The sector plays a crucial role in the nation’s economic development by providing employment opportunities to a significant number of individuals, particularly women and those with limited skills. Although significant, the contribution of this factor to the country’s GDP remains relatively modest. To maintain competitiveness in the marketplace, it is crucial to adopt a suitable marketing mix strategy. The purpose of this study is to examine the effect of marketing mix strategies on the business performance of Bangladeshi garment organisations. This investigation further assesses the role of service quality as a mediator between marketing mix strategies and firm business performance. McCarthy’s (1964) four P’s—product, place, price, and promotion—serve as the basis for this study’s marketing mix components. This study’s data were collected using a self-administered survey questionnaire. A total of 327 employees from various garment factories in CEPZ were conveniently chosen for this investigation. The data was analysed using SPSS 24.0 and Smart PLS 3.0. The study’s findings indicate that the strategies related to product, place, price, and promotion had a substantial linkage with the service quality of firms. Furthermore, the service quality significantly mediates the correlation between marketing mix strategies and the business performance of the garments industry. The findings suggest that companies can gain a competitive edge by prioritising their marketing strategies and improving the quality of their related services.